Relationships among Cumulative Life Stress, Interoception, and Psychiatric Presentations with Somatic Features - Simon, Alia (East Carolina University)
Interoceptive processes involve awareness and insight into one's physiological state, as influenced by the integration of sensations detected and interpreted by the nervous system. Since interoception involves ongoing communication between the brain and the body, research is beginning to investigate if interoceptive processes are influenced by past experiences that may have disrupted mind-body communication. For the current study, we sought to investigate whether one's accumulation of severe stressors across the lifespan may interfere with one's ability to perceive the integration of internal bodily signals accurately and adaptively, contributing to interoceptive dysregulation and bodily distrust. We sought to explore whether this dysregulation would ultimately contribute to adverse mental health outcomes that feature somatization. Research examining relations between cumulative life stress, interoceptive processes, and psychiatric presentations remains in its infancy with limited investigation. The current study sought to bridge the current gap in the literature by investigating interoceptive accuracy and interoceptive awareness as a dual mediator, partially accounting for the assumed relationship between cumulative life stress and symptoms of psychological disorders with somatic features. Given that interoceptive processes are a multidimensional construct, we examined interoceptive awareness (attentional style when interpreting and attending to internal bodily signals) and interoceptive accuracy (appraisal of one's perceived accuracy when interpreting bodily signals). Key variables of interest were explored within emerging adults, given that this is a salient developmental period marked by identity exploration with a greater propensity for the emergence of psychological presentations. A total of 575 undergraduate students at a large Southeastern university completed an online survey that examined cumulative life stressor severity, interoceptive processes (interoceptive awareness and interoceptive accuracy), and screeners assessing for symptoms of psychological disorders with somatic features (i.e., social anxiety disorder, panic disorder, depression, somatic symptom disorder, post-traumatic stress disorder, eating disorders). To our surprise, interoceptive accuracy did not demonstrate significant relationships with stress or symptoms, failing to account for the relationship between stress and symptoms. In contrast, interoceptive awareness demonstrated a significant inverse relationship with stress and symptoms while also acting as a protective mechanism, reducing the translation of stress to symptoms. Ultimately, our findings support the protective utility of one's ability to attune to bodily senses with a mindful, non-judgmental mindset as captured by interoceptive awareness. Gaining insight into interoceptive patterns associated with common psychological disorders provides insight for tailoring transdiagnostic psychometric tools and interventions informed by the mind-body connection.
Keywords: Psychological Presentations; Cumulative Life Stress; Emerging Adulthood; Interoception; Somatic symptom disorder; Undergraduates--Mental health--Southern States